MICROSYMBIONT AND MORPHOLOGICAL PHENOTYPE ANALYSIS - Ismail Marzuki (Hasanuddin University, 2016)
Determination biomass and phenotypic analysis of microsymbionts sponge is a comprehensive effort to discover the specificity of the sponge, not only on the identification and characterization studies that have been growing. Research directed at diversification of knowledge of the functions and benefits of a sponge for the life and welfare of mankind. The purpose of this research is the analysis of biomass morphology and phenotype test microsymbionts sponge. Histomorfologi analysis method to determine the type, components and composition biomass. Isolates obtained by sponge microsymbiont isolation-purification followed by phenotypic analysis through Gram staining and biochemical tests. Histomorfologi analysis results obtained sponge species is Callyspongia sp. Components and composition consists of sponge biomass fraction skeleton (spicules and cell debris) reached 69.8 %, 18.8 % sponge cell fraction and 11.3 % bacterial pellet fraction. The results of the isolation-purification microsymbiont obtained two isolates. Staining test results both isolates are Gram-positive bacteria and biochemical tests is Bacillus subtilis isolates the spherical shape large size, beige and white, while the isolates two clustered colonies are bacillus flexus jagged shape elongated, white-purple color and a separate colony. Keywords: histomorfologi, phenotype, Callyspongia sp, biomass, microsymbiont, sponge